Diseño y simulación de una lógica de control para las etapas de proceso en el tratamiento de aguas de producción mediante el uso de un PLC e interfaz gráfica - Pesca Niño, Ricardo (Universidad Antonio Nariño, 2023)
In recent years, the exploitation of hydrocarbons has become the main economic source of our country. However, oil production involves the treatment of water from the reservoirs, which poses a challenge for oil companies. Currently, many of these companies operate the Systems of Produced Water Treatment (STAP) manually, resulting in longer processing times, operational risks, and low efficiency.